Spatial and temporal characterization of sediments and hyporheic meiofauna in a section of an urban river - José Adson Andrade de Carvalho Filho; Caroline Cibelle Correia Clemente; Paulo Jorge Parreira dos Santos; Jaime Joaquim da Silva Pereira Cabral; Anderson Luiz Ribeiro de Paiva (Revista Brasileira de Recursos Hídricos)
ABSTRACT This study characterized the hyporheic zone of a stretch of the Ipojuca River through analysis of the sediments and meiofauna of this environment. Samples were collected at two points (Point 1: 8°17'28.2” S; 35°59'38.6” W and Point 2: 8°17'48.1” S; 35°56'12.2” W) and in three periods: summer (November/2018), transition period (March/2018), and winter (June/2018). The most representative material was classified as silt, varying between coarse, medium, and fine. 678 meiofauna individuals were counted, distributed in four more representative taxa, Rotifera (41%), Nematoda (40%), Annelida (11%), and Copepoda (5%). The PERMANOVA analysis indicated significant differences for the period (p = 0.0009) and space (p = 0.0261) factors. There was no significant relationship between the meiofauna community structure and hyporheic environment variables. The observed differences may be linked to water quality, which also varied between the points and periods studied.